Arabidopsis redox status in response to caterpillar herbivory - Paudel, Jamuna; Copley, Tanya; Amirizian, Alexandre; Prado, Alberto; Bede, Jacqueline C. (Frontiers in Plant Science, 2013)
Plant responses to insect herbivory are regulated through complex, hormone-mediated interactions. Some caterpillar species have evolved strategies to manipulate this system by inducing specific pathways that suppress plant defense responses. Effectors in the labial saliva (LS) secretions of Spodoptera exigua caterpillars are believed to induce the salicylic acid (SA) pathway to interfere with the jasmonic acid (JA) defense pathway; however, the mechanism underlying this subversion is unknown. Since noctuid caterpillar LS contains enzymes that may affect cellular redox balance, this study investigated rapid changes in cellular redox metabolites within 45 min after herbivory. Caterpillar LS is involved in suppressing the increase in oxidative stress that was observed in plants fed upon by caterpillars with impaired LS secretions. To further understand the link between cellular redox balance and plant defense responses, marker genes of SA, JA and ethylene (ET) pathways were compared in wildtype, the glutathione-compromised pad2-1 mutant and the tga2/5/6 triple mutant plants. AtPR1 and AtPDF1.2 showed LS-dependent expression that was alleviated in the pad2-1 and tga2/5/6 triple mutants. In comparison, the ET-dependent genes ERF1 expression showed LS-associated changes in both wildtype and pad2-1 mutant plants and the ORA 59 marker AtHEL had increased expression in response to herbivory, but a LS-dependent difference was not noted. These data support the model that there are SA/NPR1-, glutathione-dependent and ET-, glutathione-independent mechanisms leading to LS-associated suppression of plant induced defenses.